Estimation of Erosion with Geographic Information Systems (GIS) in the TAHURA RADEN SOERJO Fire Areas - heri erwantoro timor; Tatag Muttaqin; Nugroho Tri Waskitho (Universitas Muhammadiyah Malang, 2020)
The Ledug Block is one of the areas in TAHURA R Soerjo which is experiencing fire. The fire causes the existing land cover to change or decrease, with the reduced land cover, the land will be easily exposed to surface runoff. This study aims to calculate the erosion rate in the TAHURA R Soerjo Ledug Block using the USLE equation, visual presentation of erosion using the Goegraphic Information System (GIS). This research was conducted in December 2018 in the rehabilitation area of Tahura R Soerjo Priug Ledug Block, Pasuruan. The method used is the Geographic Information System (GIS) whose data is sourced from calculations with the USLE method. The results of the study are the rain erosivity index (R) obtained from the month rainfall in 2018. The soil at the study site in each SUL is dusty clay. The vegetation in the research location in each SUL is in the form of bushes and added to SUL 3 there are several trees. The average erosion rate is 0.034 tons / ha / year. Erosion hazard classes that occur at the research location are included in class I (very mild). Enriching the land cover by planting trees with tree stands needs to be done so that the land is tightly closed and better withstand surface runoff.